2016
DOI: 10.3390/ijms17091410
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Exerts a Strong Anti-Arthritic Effect on Type II Collagen-Induced Arthritis in Rats by Inhibiting Inflammatory Responses

Abstract: To investigate anti-arthritic effects of matrine isolated from the roots of S. flavescens on type II collagen-induced arthritis (CIA) in rats and to explore its related potential mechanisms, CIA rats were established and administered with matrine (20, 40 or 80 mg/kg/days, for 30 days). Subsequently, blood was collected to determine serum levels of TNF-α, IL-1β, IL-6, IL-8, IL-17A, IL-10, MMP-2, MMP-3 and MMP-9, and hind paws and knee joints were collected for histopathological examination. Furthermore, indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…Recently, a parallel study on anti‐arthritic effect of Matrine in a rat model of CIA has been reported (Pu et al, ). Although some similar findings were found by these two research groups, these two studies were performed independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a parallel study on anti‐arthritic effect of Matrine in a rat model of CIA has been reported (Pu et al, ). Although some similar findings were found by these two research groups, these two studies were performed independently.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, matrine may be valuable drug for development of new therapies for RA in the clinic. We recognize that IL‐17 responses are important for the pathogenesis of RA (Kugyelka et al, ) and matrine regulates IL‐17 responses in animal model of CIA (Pu et al, ; Xu et al, ). We are interested in further investigating whether matrine can directly regulate Th17 cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…The paw volumes of hind paw swelling were measured with a plethysmograph every 7 days. For evaluating signs of arthritis, the AA rats were assessed every 4 days for 28 days using a 5-point ordinal scale, which is a pre-established, widely used scoring system developed to evaluate the severity of adjuvant arthritis (32,33). The rat paws were examined and scored for severity, swelling, erythema and induration by a 5-point ordinal scale (scores 0-4) as follows: 0, unaffected; 1, one type of joint affected; 2, two types of joint affected; 3, three types of joint affected; 4, three types of joint affected plus maximal erythema and swelling.…”
Section: Adjuvant Arthritis (Aa) Model and Treatmentmentioning
confidence: 99%
“…In recent years, herbal therapy have been shown to be beneficial in curing various diseases [8,9]. In addition, these alternative herbal remedies are reliable, inexpensive and of low toxicities [9,10].…”
Section: Introductionmentioning
confidence: 99%